Thyroid status and TNF-alpha in post-reproductive women with COVID-19 and 12 months after the disease - N. V. Semenova; S. I. Kolesnikov; E. V. Vyrupaeva; l. F. Sholokhov; L. V. Rychkova; А. G. Petrova; M. R. Akhmedzyanova; M. A. Darenskaya; L. I. Kolesnikova (Acta Biomedica Scientifica)
The aim. To assess the thyroid status and its relationship with tumor necrosis factor alpha (TNF-alpha) in post-reproductive women in the acute phase of the COVID-19 of moderate course and 12 months after the disease.Materials and methods. 85 women aged 45 to 69 years were divided into groups: women without COVID-19, not vaccinated, with no antibodies to COVID-19 (IgG) – control group (n = 15); women in the acute phase of COVID-19 of a moderate course, accompanied by pneumonia – main group (n = 57); patients from the main group who agreed to be examined 12 months after having COVID-19 (n = 14); women with IgG in blood who deny any symptoms of COVID-19 in the last 12 months – asymptomatic COVID-19 (n = 13). Using hormone replacement therapy and the presence of thyroid disease in history were the exclusion criteria from the study.Results. 75.4 % of patients with COVID-19 had euthyroidism, 12.3 % had subclinical hyperthyroidism. An increase of free thyroxine (free T4) level in women with COVID-19 as compared to the control group (p = 0.004) and the group with asymptomatic COVID-19 (p = 0.054) was found. There was no statistically significant difference in the level of thyroid stimulating hormone between the groups. The level of C-reactive protein in women with COVID-19 was naturally higher as compared to the control group (p = 0.009) and the group of asymptomatic patients (p = 0.001). A lower TNF-alpha level was found in the group of patients without clinical signs of COVID-19 as compared to the control group (p = 0.007) and the group with COVID-19 (p = 0.00007). The analysis of correlation relationships revealed a positive correlation between of free T4 and TNF-alpha levels in women with COVID-19 (r = 0.38, p = 0.004).Conclusions. The moderate course of COVID-19 in the post-reproductive women is associated with an increase of free T4 level, which positively correlates with TNF-alpha level. Twelve months after COVID-19, thyroid status in women remains at the level of the acute phase of the disease.